A spherically shielded triphenylamine and its persistent radical cation - Schaub, Tobias A.; Mekelburg, Theresa; Dral, Pavlo O.; Miehlich, Matthias; Hampel, Frank; Meyer, Karsten; Kivala, Milan (Chemistry - a European journal, 2020)
This work reports the design and synthesis of a sterically protected triphenylamine scaffold which undergoes one-electron oxidation to form an amine-centered radical cation of remarkable stability. Several structural adjustments were made to tame the inherent reactivity of the radical cation. First, the parent propeller-shaped triphenylamine was planarized with sterically demanding bridging units and, second, protecting groups were deployed to block the reactive positions. The efficiently shielded triphenylamine core can be reversibly oxidized at moderate potentials (+0.38 V, vs. Fc/Fc+ in CH2Cl2). Spectroelectrochemistry and chemical oxidation studies were employed to monitor the evolution of characteristic photophysical features. To obtain a better understanding of the impact of one-electron oxidation on structural and electronic properties, joint experimental and computational studies were conducted, including X-ray structural analysis, electron paramagnetic resonance (EPR), and density functional theory (DFT) calculations. The sterically shielded radical cation combines various desirable attributes: A characteristic and unobstructed absorption in the visible region, high stability which enables storage for weeks without spectroscopically traceable degradation, and a reliable oxidation/re-reduction process due to effective screening of the planarized triphenylamine core from its environment.
Version of record online: February 21, 2020
Gesehen am 22.11.2021